1999
DOI: 10.1007/bf02745675
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and electrical characteristics of SiO2 doped ZnO-Bi2O3 varistors

Abstract: Varistors in the new system ZnO--Bi203--SiO2 were prepared through conventional ceramic processing route. The effect of sintering temperature and time (0.5 h to 2 h between 1000 ° and 1250°C) on the microstructure and current/voltage characteristics of the varistors of the new system were investigated and the results were compared with those of ZnO-Bi203 system varistors prepared. An increase in nonlinear coefficient (a) value was observed in the Sit 2 added varistors. The microstructure and the phase of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…With higher amounts of SiO 2 , the Zn 2 SiO 4 phase forms, a spinel phase structure, which, like the Zn 2.33 Sb 0.67 O 4 antimony spinel, restrains the growth of ZnO grains. Besides, Zn 2 SiO 4 grains offer a high electrical resistance, inhibiting both the electron transport and the mass transport of ions, so fitting the requirements for the inclusions we are seeking. Accordingly, compositions with different amounts of SiO 2 were prepared to investigate the effect of Si‐doping on the varistor leakage current.…”
Section: Resultsmentioning
confidence: 99%
“…With higher amounts of SiO 2 , the Zn 2 SiO 4 phase forms, a spinel phase structure, which, like the Zn 2.33 Sb 0.67 O 4 antimony spinel, restrains the growth of ZnO grains. Besides, Zn 2 SiO 4 grains offer a high electrical resistance, inhibiting both the electron transport and the mass transport of ions, so fitting the requirements for the inclusions we are seeking. Accordingly, compositions with different amounts of SiO 2 were prepared to investigate the effect of Si‐doping on the varistor leakage current.…”
Section: Resultsmentioning
confidence: 99%
“…2,8 For samples C-E, the effective Noticeably, SiO 2 coating may also contribute to the enhancement of a. Kutty and Ezhilvalavan 16 reported that SiO 2 addition could enhance the nonlinear coefficient of a ZnO varistor by modifying the interface trap states at the grain boundary. Goel et al 13 pointed out that SiO 2 addition enabled an increased nonlinear coefficient in the way that an intergranular SiO 2 rich phase inhibited electron transport due to its high electric resistance.…”
Section: (C) Microstructure and Electrical Properties Of Sintered Zno...mentioning
confidence: 99%
“…SiO 2 addition prompts the formation of Zn 2 SiO 4 , which could inhibit ZnO grain growth the during sintering process. [12][13][14] Meanwhile, some literature 13,[15][16][17] proposed that SiO 2 addition also promotes the improvement of the nonlinear coefficient of ZnO varistors. However, the simple way of adding SiO 2 in conventional solid mixing exhibits a finite effect on the modification of the varistor microstructure.…”
Section: Introductionmentioning
confidence: 99%